Child-friendly transparency of data processing in the EU: from legal requirements to platform policies. Issue 1 (2nd January 2020) - Milkaite, Ingrida; Lievens, Eva
ABSTRACT: Vast amounts of personal data of children are collected and processed in today's increasingly digital, connected society by public and private actors. Children do have a right to the protection of their personal data and, according to the General Data Protection Regulation (GDPR), even merit specific protection. Children should be clearly informed of and understand what happens with their data when it is collected, processed, stored and transferred. To that end, specific transparency standards require the provision of information in a clear and plain language that the child can easily understand. In this article, after having mapped these existing requirements, the privacy policies of Instagram, Snapchat and TikTok — services which are very popular with children — are evaluated. The findings suggest that such policies are still complex, long and primarily text based. In order to improve this, possible practical ways of enhancing transparency for children such as legal visualization, co-design, co-creation techniques and participatory design methods which focus on presenting legal information in a transparent and clear manner are explored.